Analisis Critical Success Factors (CSF) dari Implementasi Enterprise Resource Planning (ERP): Studi Kasus PT. Perusahaan Listrik Negara (Persero) - Firmansyah Apryadhi; Dana Indra Sensuse (Institut Teknologi PLN, 2023)
The implementation of an Enterprise Resource Planning (ERP) system has become a major requirement for companies to simplify their business processes. ERP systems have great benefits to help companies streamline business processes, increase productivity, and increase revenue. However, ERP systems are a complex systems and have a high failure rate. Therefore, every company needs to identify a critical success factor (CSF) in ERP implementation so that there are no failures that can harm the company. The purpose of this study was to analyze every 12 Critical Success Factors (CSF) at PT. Perusahaan Listrik Negara (Persero) or PT. PLN (Persero). Data collection was carried out by distributing questionnaires with an interval measurement scale using the Likert scale method on company management, ERP consultants, IT staff and users involved in the development and use of ERP systems at PT. PLN (Persero). From the 12 success factors, there are five factors that most influence the success of ERP system implementation at PT. PLN (Persero) namely Team Work, Top Management Support, User Training, Use of Consultants, and Project Management.